Hemaology, immunology, and infectious disease : neonatology questions and controversies - Ohls, Robin K. ;Maheshwari, Akhil (Philadelphia, Pennsylvania : Elsevier, Saunders, 2012)
Hematology, Immunology and Infectious Disease, a volume in Dr. Polin's Neonatology: Questions and Controversies Series, offers expert authority on some of the toughest challenges you face in your practice. This medical reference book will help you provide better evidence-based care and improve patient outcomes with research on the latest advances. Reconsider how you handle difficult practice issues with coverage that addresses these topics head on and offers opinions from the leading experts in the field, supported by evidence whenever possible. Find information quickly and easily with a consistent chapter organization. Get the most authoritative advice available from world-class neonatologists who have the inside track on new trends and developments in neonatal care. Purchase each volume individually, or get the entire 6-volume set, which includes online access that allows you to search across all titles!
Updated information on stem cells for the neonatologist -- Current issues in the pathogenesis, diagnosis, and treatment of neonatal thrombocytropenia -- Role of recombinant leukocyte colony-stimulating factors in the neonatal intensive care unit -- Nonhematopoietic effects of erythropoietin -- Why, when, and how should we provide red cell transfusions and erythropoiesis-stimulating agents to support red cell mass in neonates? -- Diagnosis and treatment of immune-mediated and non-immune-mediated hemolytic disease of the newborn -- Hematology and immunology: coagulation disorders -- A practical approach to the neutropenic neonate -- What evidence supports dietary interventions to prevent infant food hypersensitivity and allergy? -- Maternally mediated nenonatal autoimmunity -- CMV: diagnosis, treatment, and considerations on vaccine-mediated prevention -- Neonatal T cell immunity and its regulation by innate immunity and dendritic cells -- Breast milk and viral infection -- Probiotics for the prevention of necrotizing enterocolitis in preterm neonates -- The ureplasma conundrum: should we look or ignore? -- Control of antibiotic-resistant bacteria in the neonatal intensive care unit -- Neonatal fungal infections -- The use of biomarkers for detection of early-and late-onset neonatal sepsis -- Chorioamnionitis and its effects on the fetus/neonate: emerging issues and controversies
Includes bibliographical references and index.
Keywords: NEONATAL HEMATOLOGY